The Factors Associated with Knowledge of Signs of High Risk Pregnancy Trimester III in Working Area of Tebing Tinggi Public Health Center Empat Lawang Regency - Nuril Absari; Mika Oktarina; Sulistiani Sulistiani (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
High risk of pregnancy are signs that indicate a danger that may occur during pregnancy that if not reported or detected can cause maternal death. This study aimed to study factors related to knowledge of high risk sign of third trimester pregnancy in working area of Tebing Tinggi Public Health Center Sub-district of Empat Lawang Regency. This research used cross sectional design. Population in this research was all third trimester pregnant woman in working area of Tebing Tinggi Public Health Center Regency of Empat Lawang. Sampling technique used accidental sampling. Data collection in this study used primary data. Collected data were analyzed by using univariate and bivariate analysis by using chi-square test. The result showed that there were 19 mother (43.2%) with enough knowledge, 25 mother (56.8%) with age 20-35 years old, 20 mother (45,5%) with secondary education, 20 mother (45.5%) with multiparas parity, there was a significant relationship between maternal age and knowledge of high risk sign of third trimester pregnancy with moderate relationship category, there was a significant relationship between maternal education with knowledge of high risk sign of third trimester pregnancy with relationship category moderate, there was a significant relationship between pregnant mother's parity with knowledge of high risk sign of third trimester pregnancy with moderate relationship category. Keywords: age, education, knowledge, parity